Ultrasound biomicroscopy in patients with unilateral pseudoexfoliation - Erkan Ünsal; Kadir Eltutar; Ilkay Muftuoglu; Tulay Alpar Akcetin; Yıldız Acar (International Journal of Ophthalmology, 2015)
AIM: To compare the anterior segment morphology evaluated using ultrasound biomicroscopy (UBM) in patients with clinical pseudoexfoliation syndrome (XFS) in one eye and no clinical XFS in the fellow eye.METHODS: Thirty patients with unilateral XFS were included in the study. All patients underwent evaluation of their anterior segment using UBM with and without dilatation with 1% cyclopentolate. The anterior chamber depth (ACD), lens thickness (LT), anterior chamber angle (ACA), ciliary body thickness (CBT), scleral thickness (ST), trabeculae -ciliary processes distance (T-CPD), and iris-ciliary processes distance (I-CPD) were measured using UBM scans. All results between the eyes with clinical XFS and their fellow eyes without clinical XFS were then compared.RESULTS: Before dilatation the eyes with XFS (4.350±0.531 mm) were found to have a significantly thicker lens (P=0.002) than the eyes without XFS (4.238±0.540 mm). In addition after dilatation, the eyes with XFS (4.310±0.500 mm) were found to have a significantly thicker lens than the eyes without XFS (4.160±0.480 mm) (P=0.019). The average ACD, for the group with XFS, comparing pre-dilatation (2.616±0.349 mm) and post-dilatation measurements (2.714±0.413) was found to be statistically increased (P=0.014). The average ACD, comparing pre-dilatation to post-dilatation measurements in patients without XFS (2.680±0.360), (2.720±0.500) was found to be statistically unchanged (P=0.450).DISCUSSION: Crystalline lenses tended to be thicker in the eyes with clinical pseudoexfoliation than their fellow eyes without pseudoexfoliation.